Анализа корелације нивоа ЦЦЛ4, ТРАЦП-5б и ХПДР2 у серуму са негативним исходима код остеопорозе после менопаузе (ОМ): Серумски CCL4, TRACP-5b и HPDR2 код ПМОП-а - Zhu, Kejia; Sun, Jiaqu; Wang, Biao; Xing, Fei; Zhang, Hui; Deng, Tao; Wang, Junqing; Zhang, Yuqi; Yan, Dusong; Nie, Yong (Journal of Medical Biochemistry, 2026)
Objective To determine the predictive efficacy of measuring fibroblast growth factor 23 (HPDR2) in postmenopausal individuals with osteoporosis, tartrate-resistant acid phosphatase 5b (TRACP-5b), and serum macrophage inflammatory protein-1 β (CCL4) for fractures.Methods The osteoporosis group consisted of 242 postmenopausal individuals with osteoporosis who were admitted to the hospital between January 2023 and January 2025. There were two groups of patients: 108 patients with fractures and 134 patients without. The decreased bone mass group (164 patients) and the control group (130 patients) were composed of postmenopausal women who were diagnosed with decreased bone mass and normal bone mass in the hospital during the same time period. The levels of serum CCL4, TRACP-5b and HPDR2 in each group were compared. The predictive value of serum CCL4, TRACP-5b, and HPDR2 detection for fractures in postmenopausal patients with osteoporosis was assessed using univariate and multivariate analysis on the influencing factors of fractures in patients with osteoporosis. The relationships between the levels of serum CCL4, TRACP-5b and HPDR2 and the severity of fractures were analyzed.Results The levels of serum CCL4, TRACP-5b and HPDR2 in the osteoporosis group were significantly greater than those in the decreased bone mass group and the control group (P247.35 pg/mL were risk factors for fractures in postmenopausal patients with osteoporosis (P